The Effect of Using Pocket Books on Ecosystems on the Critical Thinking Skills of Seventh Grade Students - M. Abriyanto; Hodijah, Siti Romlah Noer; Vitasari, Mudmainah (PENDIPA Journal of Science Education, 2025)
The purpose of this study was to determine the effect of pocket books on critical thinking skills related to the ecosystem theme among seventh-grade junior high school students. The study was conducted at SMPN 17 City of Serang using a quasi-experimental method with a nonequivalent control group design. Research instruments included critical thinking tests and student response questionnaires. Results showed an increase in critical thinking skills in the experimental class that used the pocket book, with an average posttest score of 79.5, compared to 72 in the control class. A Mann-Whitney test revealed a significance value of 0.001 (less than 0.05), indicating a significant effect. The effect size value of 0.957 indicates a large effect. Based on these results, it can be concluded that using pocketbooks on the theme of ecosystems effectively improves students' critical thinking skills.